REMOVAL OF As (V) BY USING BOTTOM ASH AS ADSORBENT - Yildirim, Meral; Mermer, Nevin Karamahmut; Demir, Funda; Derun, Emek Moroydor (CENTRAL BOHEMIA UNIV, 2017)
Industrial development brings waste problem which is a challenge for both human health and ecological cycle. Arsenic is a toxic and carcinogenic heavy metal that should be removed from drinking or waste water. In this study, an industrial waste of bottom ash was used as an adsorbent to remove As (V). To find an appropriate adsorption conditions, the adsorption temperatures and contact time were varied between 30 degrees C-50 degrees C and 5-180 min, respectively. The experimental results were fitted to the Langmuir and Freundlich isotherms. The highest values of n and K-F for Freundlich isotherm were obtained for 30 degrees C and calculated as 0.432 and 0.006, respectively. According to kinetic studies, the kinetics of these experiments could be explained by pseudo-second order kinetic model, and the pseudo-second order rate constant was calculated as 0.034 g/mg.min, 0.033 g/mg.min and 0.030 g/mg.min for 30 degrees C, 40 degrees C and 50 degrees C, respectively. According to experimental results, bottom ash can be used for removal of As (V) from water sources.
Keywords: Adsorption; arsenic; bottom ash; ICP-OES; PERFORMANCE; WATER; Business & Economics; Public Administration